Cultural intersections in music therapy : music, health, and the person - Whitehead-Pleaux, Annette; Tan, Xueli (Barcelona Publishers, 2017)
This is the first comprehensive textbook on multicultural dimensions of music therapy. The editors pass the literary microphone to the authorsâe"all music therapists who have found belonging and identity in diverse cultures. The authors examine how music therapy is relevant within an individualâe(tm)s cultural context through personal and scholarly explorations. The chapters are separated into three sections:1. Understanding oppression and bias;2. Minority cultures within North America3. Inclusive music therapy practice and education.This focused examination prompts the reader to listen to myriad minority voices and engage in cultural dialogues. Both print and electronic versions available.
Keywords: Music therapy; Multiculturalism